2020
DOI: 10.1155/2020/2854795
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Spraying with Compound Amino Acid-Iron Fertilizer Increases Leaf Fresh Weight, Photosynthesis, and Fe-S Cluster Gene Expression in Peach (Prunus persica (L.) Batsch)

Abstract: As one of the most important micronutrients, iron (Fe) plays a critical role in various metabolic processes during plant growth and development. However, the molecular mechanisms towards Fe metabolism and nutrition in fruit trees are largely unknown. In this study, we examined the effects of amino acid-Fe compound fertilizer spraying on leaf development in peach (Prunus persica (L.) Batsch) at different developmental stages. Foliar spraying with amino acid-Fe compound fertilizer did not cause any significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…Studies have shown that exogenous Suc could enhance tolerance to Fe deficiency through regulating chlorophyll biosynthesis in Malus halliana ( Guo et al, 2020 ). Additionally, foliar spraying with amino acid-Fe compound fertilizer remarkably increased fresh weights, Fe accumulation, total chlorophyll content, photosynthesis, and stomatal conductance of leaves in peach ( P. persica L. Batsch; Sheng et al, 2020 ).…”
Section: Iron Fertilizer Improves Photosynthesis Fruit Yield and Qumentioning
confidence: 99%
“…Studies have shown that exogenous Suc could enhance tolerance to Fe deficiency through regulating chlorophyll biosynthesis in Malus halliana ( Guo et al, 2020 ). Additionally, foliar spraying with amino acid-Fe compound fertilizer remarkably increased fresh weights, Fe accumulation, total chlorophyll content, photosynthesis, and stomatal conductance of leaves in peach ( P. persica L. Batsch; Sheng et al, 2020 ).…”
Section: Iron Fertilizer Improves Photosynthesis Fruit Yield and Qumentioning
confidence: 99%
“…According to Khan et al (2019), applying amino acids to leaves increased photosynthesis efficiency and lettuce growth. The higher crop growth rate in plants can be due to the biostimulant composition, which contains various stimulants such as amino acids that can act as signaling molecules to improve fertilizer assimilation (Sheng et al, 2020). Amino acids are crucial for the growth and development of horticultural crops (du Jardin, 2015).…”
Section: Growth and Yieldmentioning
confidence: 99%
“…Biostimulants are substances that contain one or more compounds or microorganisms formulated to stimulate plant growth, as well as mechanisms for regulating plant resistance to stress conditions from both biotic and abiotic sources, improving microbiological rhizosphere activity and soil enzymes, and optimizing the photosynthesis process to improve crop production with low application doses (du Jardin, 2015;Sharma et al, 2014;Yakhin et al, 2017). The use of biostimulants has been reported can increase the activity of vital enzymes involved in the metabolism of carbon and nitrogen, hormone activity as well as physiological and biochemical changes in plant tissues (Alfosea-Simón et al, 2020;Sheng et al, 2020). In horticultural crops, the use of biostimulants enables the reduction of fertilizer without a significant reduction in yield or quality (Noroozlo et al, 2019;Souri & Bakhtiarizade, 2019), as well as increasing essential micronutrients (Fe, Cu, and Zn) for human health (Mannino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Iron (Fe) as a micronutrient plays an important role in the synthesis of chlorophyll in crops. Over the past decades, many approaches including functionalized natural product application, soil improvement, crop management, and iron fertilizer application have been applied to mitigate iron deficiency in crops. , Among them, the most efficient way is the use of Fe fertilizer to improve the Fe utilization and boost crop yield. , So far, various Fe-based fertilizers have been developed for peanut growth, such as synthetic Fe chelates, inorganic-Fe fertilizer, and organic-Fe fertilizer. ,, Although these synthetic fertilizers are effective in Fe-deficient soils, they are often associated with high costs, low efficiency, and potential environmental risks. These problems can be overcome by replacing them with new, effective, and sustainable iron-based fertilizers. , …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Among them, the most efficient way is the use of Fe fertilizer to improve the Fe utilization and boost crop yield. 13,14 So far, various Fe-based fertilizers have been developed for peanut growth, such as synthetic Fe chelates, inorganic-Fe fertilizer, and organic-Fe fertilizer. 4,15,16 Although these synthetic fertilizers are effective in Fe-deficient soils, they are often associated with high costs, low efficiency, and potential environmental risks.…”
Section: ■ Introductionmentioning
confidence: 99%